ENTACAPONE – BASED FLOATING MICROSPHERES BY IONOTROPIC GELATION TECHNIQUE-MORPHOLOGY AND RELEASE CHARACTERISTICS (International Journal of Pharmaceutical Sciences and Drug Research, 2018)
The main objective of the present investigation was to develop gastro retentive floating microspheres for Entacapone. These are prepared by ionotropic gelation method with an aim of increasing the gastric residence time and for controlled release. The polymeric mixture of Sodium alginate and HPMC K4, was used as polymers. Sodium bicarbonate was used as the gas-forming gent. Prepared Microspheres were characterized for the Micromeretic properties, incorporation efficiency, buoyancy test, SEM analysis, FTIR, and in vitro diffusion studies. The diffusion studies were carried out in 0.1N HCl and the results were applied to various kinetic models. Among the total 14 formulations F14 was optimized. The % yield of F14 formulation was found to be 98.03%. Based on optical microscopy, the particle size was 65.23 ± 0.05µm. The % buoyancy, % entrapment efficiency and swelling index of F14 formulation was 98.16%, 97.54% and 97.67%, respectively. The cumulative % drug release of F14 formulation was 97.99 ± 5.05% in 12 h when compared with marketed product 95.12 ± 5.01 in 1 h. SEM studies showed the particles were in spherical shape. Hence the formulated and prepared floating Entacapone microspheres may establish to be potential candidate for safe and effective sustained drug delivery and improve the bioavailability in the management of Parkinson’s disease.